ANALISIS PENGARUH INDEKS PEMBANGUNAN MANUSIA (IPM) DAN PRODUK DOMESTIK REGIONAL BRUTO (PDRB) TERHADAP TINGKAT KEMISKINAN DI KABUPATEN BOLAANG MONGONDOW - Renaldi; Tawas, Yance; Malau, Natalia (Program Studi Ilmu Ekonomi, 2023)
The objective of this study was to evaluate whether or not the HDI, GRDP, and poverty rates of the Bolaang Mongondow area were all connected to one another. Information from the Central Statistics Agency is included among the primary and secondary sources that were utilized for this article. In order to carry out the statistical study, SPSS 26's Multiple Linear Regression Model was used. According to the findings of this study, (1) the Human Development Index (HDI) and regional Gross Domestic Product (GDP) have a considerable impact on poverty rates, (2) GDP has a negative influence on poverty rates, and (3) both have an effect. The findings of the research indicate that the development plan for the Bolaang Mongondow District should place a greater emphasis on two independent variables if it is to be successful in reducing the level of poverty in that area. There will be some growth in terms of economic activity in the Bolaang Mongondow region.